Raman scattering spectrum detection chip as well as preparation method and application thereof

By introducing a composite structure of BiFeO3 film and precious metal nanoparticle array into the Raman scattering spectral detection chip, the problem of low sensitivity of existing detection chips is solved, and high sensitivity detection of trace chemicals is achieved.

CN119534426APending Publication Date: 2025-02-28ZHENGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411961212.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing Raman scattering spectroscopy detection chip has low detection sensitivity and cannot meet the needs of trace chemical detection.

Method used

A composite surface-enhanced Raman scattering spectral detection chip is designed, with a structure consisting of a substrate, a BiFeO3 film and a precious metal nanoparticle array. The built-in electric field of BiFeO3 film promotes charge transfer, and the precious metal nanoparticle array enhances the Raman signal through local plasmon resonance coupling effect.

Benefits of technology

Through the dual enhancement mechanism, the intensity of the Raman scattering spectral signal is significantly improved, and the sensitivity of detecting trace organic molecules is increased by at least one order of magnitude.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119534426A_ABST
    Figure CN119534426A_ABST
Patent Text Reader

Abstract

The invention provides a Raman scattering spectrum detection chip as well as a preparation method and application thereof, and belongs to the technical field of Raman scattering spectrums. The Raman scattering spectrum detection chip sequentially comprises a substrate, a BiFeO3 film and a noble metal nanoparticle array from bottom to top. The preparation method comprises the following steps: mixing bismuth salt, ferric salt and ethylene glycol monomethyl ether in acetic acid to obtain a precursor solution; spin-coating the precursor solution on a substrate to prepare a film, annealing after spin-coating each layer, repeating the spin-coating and annealing processes until the required thickness is reached, and finally performing heat treatment to prepare a BiFeO3 film; and dropping noble metal nano-particle dispersion liquid on the surface of the BiFeO3 film, and then drying to obtain the Raman scattering spectrum detection chip. The Raman scattering spectrum signal intensity of the Raman scattering spectrum detection chip disclosed by the invention is remarkably improved, and the sensitivity of the Raman scattering spectrum detection chip can be improved by at least one order of magnitude when the Raman scattering spectrum detection chip is used for detecting a trace organic molecule rhodamine 6G solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of Raman scattering spectrum, and in particular to a Raman scattering spectrum detection chip and a preparation method and application thereof. Background Art

[0002] Surface enhanced Raman scattering spectroscopy (SERS) is a spectral technique that can greatly enhance Raman scattering signals. It is mainly based on the localized surface plasmon resonance effect of noble metal nanostructures (nanoparticles, nanorods, etc.), which enhances the electric field near the surface of the noble metal nanostructure, thereby significantly enhancing the Raman scattering signal of the molecules to be detected adsorbed near the noble metal nanostructure (it can be enhanced by tens of thousands of times or even more), so that it is possible to detect molecules at extremely low concentrations. Therefore, surface enhanced Raman scattering spectroscopy (SERS) is widely used in many aspects such as biomolecule detection, environmental monitoring, food safety testing, etc., and can achieve high-sensitivity and high-selectivity detection and analysis of trace substances.

[0003] At present, detection chips based on Raman scattering spectroscopy technology are usually prepared from noble metal nanoparticles, mainly using the localized plasma resonance coupling effect between noble metal nanoparticles to enhance the Raman signal of molecules near their surface, which is called "surface enhanced Raman scattering spectroscopy (SERS)". This mechanism of enhancing Raman scattering signals is called "physical enhancement". Studies have found that this surface enhanced Raman scattering spectroscopy (SERS) detection technology based on a single enhancement mechanism has limited enhancement of the Raman signal of the analyte molecules, which greatly limits the detection sensitivity of the surface enhanced Raman scattering spectroscopy (SERS) detection chip, thereby hindering its application in real detection scenarios. Recently, a new type of "chemically enhanced Raman scattering spectroscopy" effect and mechanism has attracted widespread attention from researchers. The mechanism of this "chemical enhancement" is that charge transfer occurs between semiconductor materials and surface adsorbed molecules, changing the electron cloud distribution or chemical bond properties of the analyte molecules, so that certain Raman modes of the analyte molecules are significantly enhanced, thereby improving the Raman scattering signal of the analyte molecules.

[0004] The surface enhanced Raman scattering spectroscopy (SERS) detection technology reported in current research is basically based on a single enhancement mechanism. Obviously, the surface enhanced Raman scattering spectroscopy (SERS) detection chip based on a single enhancement mechanism can no longer fully meet the needs of trace chemical substance detection. Therefore, the design and development of a composite surface enhanced Raman scattering spectroscopy (SERS) detection technology with a dual enhancement mechanism is a key technical problem that needs to be solved in this field. Summary of the invention

[0005] The object of the present invention is to provide a Raman scattering spectrum detection chip and a preparation method and application thereof, so as to solve the problem of low detection sensitivity of the Raman scattering spectrum detection chip in the prior art.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The invention provides a Raman scattering spectrum detection chip. The Raman scattering spectrum detection chip comprises, from bottom to top, a substrate, a BiFeO3 film and a noble metal nanoparticle array.

[0008] Preferably, the thickness of the BiFeO3 film is 200-500 nm; and the substrate is a single crystal silicon wafer.

[0009] The present invention also provides a method for preparing the above-mentioned Raman scattering spectrum detection chip, comprising the following steps:

[0010] S1: mixing bismuth salt, iron salt and ethylene glycol methyl ether in acetic acid to obtain a precursor solution;

[0011] S2: Spin coating the precursor solution on the substrate to form a film, annealing after each spin coating, repeating the spin coating and annealing process until the desired thickness is reached, and finally performing heat treatment to obtain a BiFeO3 film;

[0012] S3: Drop a dispersion of noble metal nanoparticles on the surface of the BiFeO3 film, and then dry it to obtain a Raman scattering spectrum detection chip.

[0013] Preferably, in step S2, the amount of the precursor solution is 0.1-0.5 mL / cm 2 .

[0014] Preferably, in step S2, the process parameters of spin coating are: firstly, spin coating is performed at a rotation speed of 500-700 rpm for 6-12 s, and then spin coating is performed at a rotation speed of 3000-5000 rpm for 20-40 s.

[0015] Preferably, in step S2, annealing includes a first annealing and a second annealing; the temperature of the first annealing is 150-250°C, and the time is 1-3 minutes; the temperature of the second annealing is 550-650°C, and the time is 4-6 minutes.

[0016] Preferably, in step S2, the heat treatment temperature is 550-650° C. and the time is 20-40 min.

[0017] Preferably, in step S3, the particle size of the noble metal nanoparticles is 35-50 nm; and the concentration of the noble metal nanoparticle dispersion is 1-3 g / L.

[0018] Preferably, in step S3, the amount of the noble metal nanoparticle dispersion is 2.5 to 12.5 μL / cm 2The drying is carried out in air for 2 to 5 hours.

[0019] The present invention also provides an application of the above-mentioned Raman scattering spectrum detection chip in trace detection.

[0020] Beneficial effects of the present invention:

[0021] (1) The Raman scattering spectrum detection chip of the present invention comprises, from bottom to top, a substrate, a BiFeO3 film and a noble metal nanoparticle array, wherein the middle layer is a semiconductor BiFeO3 film. The built-in electric field induced by the ferroelectric spontaneous polarization of BiFeO3 can efficiently separate the carriers in the film, which helps to promote the charge transfer between the semiconductor and the molecules to be measured, and change the electron cloud or chemical bond properties of the organic molecules to be measured, thereby improving the effect of the "chemically enhanced" Raman scattering signal.

[0022] (2) The role of the noble metal (Au or Ag) nanoparticle array: First, as the "physical enhancement" part of the Raman scattering signal, it enhances the Raman scattering signal of the organic molecules adsorbed near the noble metal nanoparticles through the local plasma resonance coupling effect; second, as a good electron acceptor, it accepts the migrated electrons from the organic molecules and transfers them to the semiconductor bismuth ferrite (BiFeO3) film, realizing the charge transfer between "organic molecules-semiconductor", realizing the "chemical enhancement" effect of the Raman scattering signal, and further improving the Raman scattering signal of the organic molecules to be tested, thereby achieving the role of "double enhancement".

[0023] (3) Compared with the single surface enhanced Raman scattering spectroscopy technology of precious metal nanoparticles, the intensity of the Raman scattering spectroscopy signal of the Raman scattering spectroscopy detection chip of the present invention has been significantly increased. When detecting trace organic molecules-Rhodamine 6G (R6G) solution, its sensitivity can be improved by at least one order of magnitude. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The microscopic morphology and structural schematic diagram of the Raman scattering spectrum detection chip prepared in Example 1;

[0025] Figure 2 This is a comparison chart of the Raman scattering spectrum signals of the Raman scattering spectrum detection chip of Example 1 and Comparative Example 1 testing the limit concentration R6G solution. DETAILED DESCRIPTION

[0026] The invention provides a Raman scattering spectrum detection chip. The Raman scattering spectrum detection chip comprises, from bottom to top, a substrate, a BiFeO3 film and a noble metal nanoparticle array.

[0027] In the present invention, the thickness of the BiFeO3 film is 200-500nm; and the substrate is a single crystal silicon wafer.

[0028] The present invention also provides a method for preparing the above-mentioned Raman scattering spectrum detection chip, comprising the following steps:

[0029] S1: mixing bismuth salt, iron salt and ethylene glycol methyl ether in acetic acid to obtain a precursor solution;

[0030] S2: Spin coating the precursor solution on the substrate to form a film, annealing after each spin coating, repeating the spin coating and annealing process until the desired thickness is reached, and finally performing heat treatment to obtain a BiFeO3 film;

[0031] S3: Drop a dispersion of noble metal nanoparticles on the surface of the BiFeO3 film, and then dry it to obtain a Raman scattering spectrum detection chip.

[0032] In the present invention, in step S1, bismuth salt, iron salt and ethylene glycol methyl ether are mixed in acetic acid, preferably bismuth salt and iron salt are mixed in acetic acid for the first time and then ethylene glycol methyl ether is added for the second time to obtain a precursor solution.

[0033] In the present invention, the specific types of the bismuth salt and the iron salt are not particularly limited, as long as they are bismuth salts and iron salts that can be dissolved in acetic acid. In the present invention, bismuth nitrate pentahydrate and iron nitrate nonahydrate are preferably used.

[0034] In the present invention, the molar ratio of the bismuth nitrate pentahydrate to the ferric nitrate nonahydrate is 1:1; the volume ratio of the mass of the ferric nitrate nonahydrate to acetic acid is 4.5-5.0 g:20 mL; the volume ratio of the acetic acid to ethylene glycol methyl ether is 20:10-50, preferably 20:20-40, and more preferably 20:30.

[0035] In the present invention, the first stirring and mixing time is 20 to 40 minutes, preferably 30 minutes; the second stirring and mixing time is 2 to 4 hours, preferably 3 hours.

[0036] In the present invention, in step S2, the amount of the precursor solution is 0.1-0.5 mL / cm 2 , preferably 0.2 to 0.4 mL / cm 2 , more preferably 0.25 to 0.35 mL / cm 2 .

[0037] In the present invention, in step S2, the process parameters of spin coating are: firstly spin coating at a rotation speed of 500-700 rpm for 6-12 s, and then spin coating at a rotation speed of 3000-5000 rpm for 20-40 s. Preferably, firstly spin coating at a rotation speed of 550-650 rpm for 8-10 s, and then spin coating at a rotation speed of 3500-4500 rpm for 25-35 s.

[0038] In the present invention, in step S2, annealing includes a first annealing and a second annealing; the temperature of the first annealing is 150-250°C, preferably 200°C, and the time is 1-3 minutes, preferably 2 minutes; the temperature of the second annealing is 550-650°C, preferably 550°C, 600°C, 650°C, and the time is 4-6 minutes, preferably 5 minutes.

[0039] In the present invention, in step S2, the heat treatment temperature is 550-650°C, preferably 550°C, 600°C, 650°C, and the time is 20-40 min, preferably 25-35 min, and more preferably 30 min.

[0040] In the present invention, in step S3, the particle size of the noble metal nanoparticles is 35 to 50 nm; the concentration of the noble metal nanoparticle dispersion is 1 to 3 g / L, preferably 1.5 to 2.5 g / L, and more preferably 1.64 to 2.0 g / L.

[0041] In the present invention, the noble metal nanoparticles are gold nanoparticles or silver nanoparticles, preferably gold nanoparticles.

[0042] In the present invention, the preparation method of the gold nanoparticles is as follows: dissolving trisodium citrate in water, boiling and adding tetrachloroauric acid trihydrate in batches until the reaction is complete, and leaving the solution after the reaction to stand at room temperature for 12 hours to obtain a gold nanoparticle precursor solution; centrifuging and ultrasonically cleaning the gold nanoparticle precursor solution to obtain gold nanoparticles.

[0043] In the present invention, in step S3, the amount of the noble metal nanoparticle dispersion is 2.5 to 12.5 μL / cm 2 The drying is carried out in air for 2 to 5 hours, preferably 3 to 4 hours.

[0044] The present invention also provides an application of the above-mentioned Raman scattering spectrum detection chip in trace detection.

[0045] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0046] In the embodiment of the present invention, a gold nanoparticle dispersion is preferably used, and the preparation method is as follows: 0.01g of trisodium citrate is dissolved in 150mL of deionized water to obtain a solution, which is boiled for 15min, and 1mL of trihydrate tetrachloroauric acid solution (concentration of 25mM) is quickly added under vigorous stirring. After 30s, the solution turns light red, and then 3mL of trihydrate tetrachloroauric acid solution (concentration of 25mM) is added, and stirring is continued for 10min to ensure that the reaction is complete. The reacted solution is allowed to stand at room temperature for 12h to obtain a gold nanoparticle precursor solution; the above 9mL of the gold nanoparticle precursor solution is centrifuged at 11000rpm for 12min, and after the centrifugation, the supernatant is sucked away and 8mL of deionized water is added. After ultrasonication for 5min, the centrifugation process is repeated according to the above conditions to purify the gold nanoparticles. The gold nanoparticles obtained after centrifugation are ultrasonically dispersed with 1mL of deionized water to obtain a gold nanoparticle dispersion with a concentration of 1.64g / L, wherein the particle size of the gold nanoparticles is 35-50nm.

[0047] Example 1

[0048] Weigh 4.85 g of Bi(NO3)3·5H2O and 4.04 g of Fe(NO3)3·9H2O into 20 mL of anhydrous acetic acid and stir for 30 min. Then, add 30 mL of ethylene glycol methyl ether to the mixed solution and stir for another 3 hours to form a uniform and transparent precursor solution.

[0049] A cleaned single crystal silicon wafer (size: 2×2 cm) was fixed on the chuck of the spin coater, 1 mL of the above precursor solution was dropped on the single crystal silicon wafer to make the solution completely infiltrate the surface of the single crystal silicon wafer, and then the single crystal silicon wafer was rotated at a speed of 600 rpm for 9 seconds, and then at a speed of 4000 rpm for 30 seconds, so as to obtain a uniform liquid film on the surface of the single crystal silicon wafer, and then it was placed on a heating table at 200°C for annealing for 2 minutes, and then annealed in a muffle furnace at 550°C for another 5 minutes, and the above spin coating and annealing process was repeated 12 times, and finally heat treated in a muffle furnace at 550°C for 30 minutes to obtain a BiFeO3 film with a thickness of 390 nm.

[0050] Take 10 μL of a gold nanoparticle dispersion with a concentration of 1.64 g / L (the particle size of the gold nanoparticles is 35-50 nm), drop it on the surface of the BiFeO3 film, and dry it in air for 3 hours to obtain a Raman scattering spectrum detection chip, which is recorded as an "Au nanoparticle / BiFeO3 film / Si" composite SERS chip.

[0051] Example 2

[0052] Weigh 4.85 g of Bi(NO3)3·5H2O and 4.04 g of Fe(NO3)3·9H2O into 20 mL of anhydrous acetic acid and stir for 30 min. Then, add 30 mL of ethylene glycol methyl ether to the mixed solution and stir for another 3 hours to form a uniform and transparent precursor solution.

[0053] A cleaned single crystal silicon wafer (size: 2×2 cm) was fixed on the chuck of the spin coater, 1 mL of the above precursor solution was dropped on the single crystal silicon wafer to make the solution completely infiltrate the surface of the single crystal silicon wafer, and then the single crystal silicon wafer was rotated at a speed of 600 rpm for 9 seconds, and then at a speed of 4000 rpm for 30 seconds, so as to obtain a uniform liquid film on the surface of the single crystal silicon wafer, and then it was placed on a heating table at 200°C for annealing for 2 minutes, and then annealed in a muffle furnace at 600°C for another 5 minutes, the above spin coating and annealing process was repeated 9 times, and finally heat treated in a muffle furnace at 600°C for 30 minutes to obtain a BiFeO3 film with a thickness of 370 nm.

[0054] Take 30 μL of a gold nanoparticle dispersion with a concentration of 1.64 g / L (the particle size of the gold nanoparticles is 35-50 nm), drop it on the surface of the BiFeO3 film, and dry it in air for 3 hours to obtain a Raman scattering spectrum detection chip.

[0055] Example 3

[0056] Weigh 4.85 g of Bi(NO3)3·5H2O and 4.04 g of Fe(NO3)3·9H2O into 20 mL of anhydrous acetic acid and stir for 30 min. Then, add 30 mL of ethylene glycol methyl ether to the mixed solution and stir for another 3 hours to form a uniform and transparent precursor solution.

[0057] A cleaned single crystal silicon wafer (size: 2×2 cm) was fixed on the chuck of the spin coater, 1 mL of the above precursor solution was dropped on the single crystal silicon wafer to make the solution completely infiltrate the surface of the single crystal silicon wafer, and then the single crystal silicon wafer was rotated at a speed of 600 rpm for 9 seconds, and then at a speed of 4000 rpm for 30 seconds, so as to obtain a uniform liquid film on the surface of the single crystal silicon wafer, and then it was placed on a heating table at 200°C for annealing for 2 minutes, and then annealed in a muffle furnace at 650°C for another 5 minutes, the above spin coating and annealing process was repeated 6 times, and finally heat treated in a muffle furnace at 650°C for 30 minutes to obtain a BiFeO3 film with a thickness of 320 nm.

[0058] Take 50 μL of a gold nanoparticle dispersion with a concentration of 1.64 g / L (the particle size of the gold nanoparticles is 35-50 nm), drop it on the surface of the BiFeO3 film, and dry it in air for 3 hours to obtain a Raman scattering spectrum detection chip.

[0059] Comparative Example 1

[0060] Take 10 μL of a gold nanoparticle dispersion with a concentration of 1.64 g / L (the particle size of the gold nanoparticles is 35-50 nm), drop it on the surface of a single crystal silicon wafer, and dry it in air for 3 hours to obtain a Raman scattering spectrum detection chip, which is recorded as an "Au nanoparticle / Si" SERS chip.

[0061] Figure 1 The microscopic morphology of the Raman scattering spectrum detection chip prepared in Example 1 and its structural schematic diagram are shown.

[0062] The Raman scattering spectrum detection chip of Example 1 and Comparative Example 1 was used to detect the R6G solution. The detection process and its detection process parameters were as follows: the Horiba JobinYvon confocal micro-Raman spectrometer used had an excitation wavelength of 532 nm, a laser output power of 1 mW, and a spectral resolution of 1 cm -1 The laser is focused on the detection area of ​​the sample through a 10x objective lens, and the spot diameter on the sample is 1 μm; the time interval for collecting spectral data for each sample is 1 s, and the scanning range is 400 to 1800 cm -1 The test results are as follows: Figure 2 As shown. Figure 2 It can be seen that the Raman scattering spectrum detection chip of Example 1 can detect the limit concentration of R6G solution to be 10 -9 M (mol / L), and the Raman spectrum characteristic peak of R6G is clearly visible. The Raman scattering spectrum detection chip of Comparative Example 1 can only detect the limit concentration of R6G solution of 10 -8 M (mol / L), and the characteristic peak of the Raman spectrum of R6G is very weak. This shows that the dual-synergistic composite surface-enhanced Raman scattering spectrum detection chip of the present invention can greatly improve the detection sensitivity of trace chemical substances, and the sensitivity can be improved by at least one order of magnitude.

[0063] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A Raman scattering spectrum detection chip, characterized in that: The Raman scattering spectrum detection chip comprises a substrate, a BiFeO3 film and a noble metal nanoparticle array from bottom to top.

2. The Raman scattering spectrum detection chip according to claim 1, characterized in that: The thickness of the BiFeO3 film is 200-500nm; the substrate is a single crystal silicon wafer.

3. The method for preparing the Raman scattering spectrum detection chip according to claim 1 or 2, characterized in that: The steps include: S1: mixing bismuth salt, iron salt and ethylene glycol methyl ether in acetic acid to obtain a precursor solution; S2: Spin coating the precursor solution on the substrate to form a film, annealing after each spin coating, repeating the spin coating and annealing process until the desired thickness is reached, and finally performing heat treatment to obtain a BiFeO3 film; S3: Drop a dispersion of noble metal nanoparticles on the surface of the BiFeO3 film, and then dry it to obtain a Raman scattering spectrum detection chip.

4. The method for preparing a Raman scattering spectrum detection chip according to claim 3, characterized in that: In step S2, the amount of the precursor solution is 0.1-0.5 mL / cm 2 .

5. The method for preparing a Raman scattering spectrum detection chip according to claim 4, characterized in that: In step S2, the process parameters of spin coating are: firstly, spin coating is performed at a rotation speed of 500-700 rpm for 6-12 s, and then spin coating is performed at a rotation speed of 3000-5000 rpm for 20-40 s.

6. The method for preparing a Raman scattering spectrum detection chip according to claim 4 or 5, characterized in that: In the step S2, the annealing includes a first annealing and a second annealing; the temperature of the first annealing is 150-250°C, and the time is 1-3 minutes; the temperature of the second annealing is 550-650°C, and the time is 4-6 minutes.

7. The method for preparing a Raman scattering spectrum detection chip according to claim 6, characterized in that: In step S2, the heat treatment temperature is 550-650° C. and the time is 20-40 minutes.

8. The method for preparing a Raman scattering spectrum detection chip according to claim 5 or 7, characterized in that: In the step S3, the particle size of the noble metal nanoparticles is 35-50 nm; and the concentration of the noble metal nanoparticle dispersion is 1-3 g / L.

9. The method for preparing a Raman scattering spectrum detection chip according to claim 3, characterized in that: In step S3, the amount of the noble metal nanoparticle dispersion is 2.5 to 12.5 μL / cm 2 The drying is carried out in air for 2 to 5 hours.

10. Use of the Raman scattering spectrum detection chip according to claim 1 or 2 in trace detection.